2011
DOI: 10.1002/jid.1795
|View full text |Cite
|
Sign up to set email alerts
|

Does ‘DAC-Ability’ Really Matter? The emergence of non-DAC Donors: Introduction to Policy Arena

Abstract: This article provides a state of the art on the emergence of non-Development Assistance Committee (DAC) donors and the extent to which their aid activities conform to OECD Development Assistance Committee norms (DAC-ability). It outlines the main dimensions and lines of debate regarding the relationship between the DAC, and those donors that are non-DAC members and situates the papers in this policy arena. It identifies the soft law that guides the DAC's norms and standards before summarising the key debates a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(49 citation statements)
references
References 34 publications
0
43
0
5
Order By: Relevance
“…However, this does not explain the cases of Japan, Switzerland and the US, whose level of compliance with PD targets were low even though they are considered to be traditional DAC donors. It seems then that it is the similar administrative arrangements and institutional structures of the European Union (EU) countries, rather than "DAC-ability" per se, which determines levels of compliance with DAC norms (Kim and Lightfoot, 2011;Rowlands, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this does not explain the cases of Japan, Switzerland and the US, whose level of compliance with PD targets were low even though they are considered to be traditional DAC donors. It seems then that it is the similar administrative arrangements and institutional structures of the European Union (EU) countries, rather than "DAC-ability" per se, which determines levels of compliance with DAC norms (Kim and Lightfoot, 2011;Rowlands, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…As noted above, non-EU countries do not appear to conform to OECD DAC principles such as those contained in the PD and the final monitoring survey result demonstrated that countries like the UK, Sweden and Denmark show higher levels of implementation compared to non-EU countries such as the US, Japan and Korea (see OECD, 2011a). However, Korea shares much in common with other non-European countries in that its aid systems is relatively diffuse and uncoordinated in comparison to those of so-called traditional European DAC members (Kim and Lightfoot, 2011;Rowlands, 2008). On top of that, most case studies of non-compliant countries have focused on traditional donors, but we have as yet relatively little understanding of whether theories built upon the European experience are commensurate with non-European cases such as Korea.…”
Section: Introductionmentioning
confidence: 99%
“…There is no denying that development assistance is no longer a domaine reservé for developed countries sitting on the OECD-DAC. The DAC official development assistance enjoyed near-exclusive dominance in the 1990s, but a handful of non-DAC countries have become consequential aid providers since the 2000s (Kim and Lightfoot 2011). China has transitioned from an aid recipient to a 'net donor' (Chin 2012) and is unquestionably in the vanguard among the non-DAC donors, although the volume of its foreign aid, falling within the scope of SouthSouth cooperation, remains opaque and relatively modest in contrast to heavyweight DAC members (Kitano 2014).…”
Section: Social Competition: Is the Aiib A Competing Initiative?mentioning
confidence: 99%
“…Especially with regard to divergence, an implicit assumption may be that localisation of MDGs by traditional donors (as powerful decision makers) is relatively even. This underlying assumption raises an important question of how the rest of the world is largely regarded as decision/norm takers (Kim and Lightfoot, : 713‐714; Mawdsley, :190). It has somewhat obscured non‐traditional partners' attempts or participation as decision/norm makers (Wade, ; Lee, ; Kim, ; Reilly, ).…”
Section: Conceptualising Discrepancy and Unevennessmentioning
confidence: 99%